Non surgical management for massive gastric lipomatosis. (2020) - Solano, Jaime; Herrera, Gabriel; Cadena, Manuel; Cabrera, Luis Felipe; Isaac, Efrain; Pedraza, Mauricio
Highlights: Massive gastric lipomatosis represent 5% of gastrointestinal tract lipomas and less than 1% of all gastric tumors. Early diagnose and multidisciplinary follow up, is reflected is an adequate evolution. Asymptomatic massive gastric lipomatosis, could be follow with endoscopy. Abstract: Background: Gastric lipomatosis (GL) is defined as a lipomatous lesion with diffuse infiltration of the submucosal layer by adipose tissue with multiple lesions and must be differentiated from gastrointestinal lipomas, which are solitary submucosal masses composed of well-differentiated adipose tissue surrounded by a fibrous capsule. GL are uncommon, represents 5 % of gastrointestinal tract lipomas and less than 1∼3 % of all gastric tumors. Case presentation: A 65-year-old woman, who underwent non-operatively approach by Gastric lipomatosis. Non-specific gastrointestinal symptoms and endoscopic examination ruled out the possibility of mucosal ulceration or bleeding. Endoscopic ultrasonography and abdominal CT that confirmed gastric lipomatosis. Discussion: Gastric lipomas are usually small, solitary and asymptomatic, and are hence often detected incidentally, surgical management in asymptomatic patients still be a in debate. Conclusion: Non operative management in massive gastic lipomatosis is appropiate when the patient is asymptomatic without mucosal ulceration, regardless of the amount of gastric lipomas. Avoiding patient the morbidity of a total gastrectomy.